(untitled) (Proceedings of Voronezh State University. Series: Geology, 2018)
The paper presents the results of gravimetric and magnetometric studies of the Pulytinskoye seismic ring anomaly revealed in 2007 to the north of Tyumen. Detailed measurements of the gravitational and magnetic fields are carried out along two orthogonally intersecting profiles crossing in the center of the ring structure. Within the seismic anomaly, the gravitational field is extremely different from the outer surrounding spaces. There is a high-frequency change of positive and negative annular anomalies. In a magnetic field Pulytinskoye seismic anomaly corresponds to a positive anomaly with an amplitude of 225 nT. Complex analysis of the morphology of potential fields, seismic and geochemical materials and other types of surveys allows us to speak about the impact nature of the seismic anomaly, as a result of the meteoric fall.